Calcium Handling in Airway Smooth Muscle: Mechanisms and Therapeutic Implications - Luke J Janssen (Canadian Respiratory Journal)
Calcium plays a central role in the activation of many cellular processes, including the most relevant end-point in airway smooth muscle physiology: contraction. For this reason, the cytosolic concentration of calcium is tightly controlled by an elaborate array of mechanisms. The latter include multiple entry pathways from the extracellular space, a pump on the membrane that extrudes calcium out of the cell, an internal pump that sequesters calcium into an intracellular pool and at least two types of release sites from which sequestered calcium can be released back into the cytosol; all of these mechanisms are tightly regulated by second messenger-signalling pathways. Understanding of the relationship between calcium handling and contraction ("excitation-contraction coupling") has progressed from a mechanism in which activation of voltage-dependent calcium channels plays a central role (as in skeletal muscle) to a mechanism in which a small localized signalling event triggers a massive release of internal calcium (as in cardiac muscle) to a more complicated model in which the internal calcium pool divides the cytosol into two physiologically distinct spaces where the cytosolic concentration of calcium is regulated independently (as in vascular smooth muscle). The changes that may occur in calcium-handling pathways in asthma and the opportunities for novel approaches to the treatment of asthma are also discussed.